Penerapan Rantai Markov Pada Pola Perpindahan Pembelian di Produk Songkok - Agustina, Fitri; Novianti, Trisita (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2022)
The projected decrease inspired this research in Afdhol MSMEs' consumer base in 2020. This study's objectives were to determine the pattern of product brand transfer for Nasional Afdhol (SNA) and predict the market share and price of prayer cap products. This study was undertaken at the SNA in Bungah District, Gresik Regency. With a population of 415 people and a required sample size of 204 persons, the required data consists of a questionnaire containing questions concerning prayer cap brand items used in the past and prayer cap brand products used presently. There are three competing prayer cap brands: Nasional ONH, Pendopo, and Nasional Gapuro Bungah. During the pandemic, it has decreased drastically by almost 70% until the last two years, so the problem that can be formulated was SNA has never evaluated the market, so competitors have never been taken into account for their role, which may affect the market share, and how consumers behave in their role in choosing which songkok to buy. By calculating using the Markov chain, the pattern of songkok purchase movement made by consumers in the 4 songkok brands can be analyzed so that SNA canplan marketing strategies to increase sales and their expected values. Data processing was performed using Rantai Markov, beginning with projecting market share using three strategies. The first strategy was without decreasing or raising prices. The second strategy was reducing the price of Rp. 5,000.00, and the third strategy was increasing the price of Rp. The calculation results yielded the greatest market share value. A formulated strategy was to cut the price of Rp. 5,000.00 by 42.65% with a probability value of 0.4265 under a steady-state condition of 0.4714 with a profit of Rp. 1,137,636. The strategy to obtain maximum expectation values has the consequence of enlarging its customer base.